Advanced Progress in the Role of Adipose-Derived Mesenchymal Stromal/Stem Cells in the Application of Central Nervous System Disorders - Haiyue Wu; Yishu Fan; Mengqi Zhang (MDPI AG, 2023)
Currently, adipose-derived mesenchymal stromal/stem cells (ADMSCs) are recognized as a highly promising material for stem cell therapy due to their accessibility and safety. Given the frequently irreversible damage to neural cells associated with CNS disorders, ADMSC-related therapy, which primarily encompasses ADMSC transplantation and injection with exosomes derived from ADMSCs or secretome, has the capability to inhibit inflammatory response and neuronal apoptosis, promote neural regeneration, as well as modulate immune responses, holding potential as a comprehensive approach to treat CNS disorders and improve prognosis. Empirical evidence from both experiments and clinical trials convincingly demonstrates the satisfactory safety and efficacy of ADMSC-related therapies. This review provides a systematic summary of the role of ADMSCs in the treatment of central nervous system (CNS) disorders and explores their therapeutic potential for clinical application. ADMSC-related therapy offers a promising avenue to mitigate damage and enhance neurological function in central nervous system (CNS) disorders. However, further research is necessary to establish the safety and efficacy of clinical ADMSC-based therapy, optimize targeting accuracy, and refine delivery approaches for practical applications.